New challenges in the implementation of policies of environmental sanitation - Chamizo García, Horacio Alejandro (2009)
The most important results of a bibliographical revision about public policy management of environmental sanitation in human settlements are presented. The revision was proposed to identify determinant factors of the management in studies carried out in diverse countries and particularly in Latin America, using new institutionalism approach and its different theoretical point of view: historical, sociological, normative and rational choice. As main results, papers considers: resistance facing the new ideas of strategic actors associated with dominant paradigms and its socialization. It discusses also about influence of formal normative framework and particularly design of the spaces of interaction among social and administrative sectors for approach to environmental sanitation since a complex perspective. The paper show evidences of the agency relations in conditions of pseudo markets and its influence at policy network. It explains main factors of management of public policy, relevant for health and for reduction of social inequity.